TRANSARTERIAL CHEMOEMBOLISATION FOR THE TREATMENT OF HEPATOCELLULAR CANCER IN NORTHERN IRELAND: OUTCOMES FROM A REGIONAL REFERRAL CENTRE. (8th June 2013) - Stratton, L; Bhat, S K; Cash, W J; Cadden, I S; Kennedy, P; Ellis, P K; Collins, A; Gavin, A; McDougall, N I
Abstract : Introduction: Transarterial chemoembolisation (TACE) is often used to palliate patients with inoperable hepatocellular cancer (HCC) and may be used as a holding procedure prior to transplantation. All TACE therapy in Northern Ireland (NI) is delivered by a single centre. Aims/Background: To determine the outcomes for patients in NI treated with TACE for HCC since 2006. Method: Patients with HCC diagnosed between 1 January 2006 and 30 November 2011 who underwent TACE in NI were identified. Case records were reviewed and the regional NI cancer registry database used for mortality data. Results: 78 patients (82% male, mean age 66.3 years) with HCC were included. Mean number of treatments was 2.2 (range 1–6). The number treated each year from 2006 was 6, 11, 15, 14, 14 and 18 in 2011. Conclusion: There has been a progressive increase in use of TACE for HCC treatment in NI since 2006. ALD was the most common aetiology. Mortality at 2 years was 67% which compares favourably with published studies.